Gen Z’s Interest in Buying Le Minerale Products: Seen From The Influence of Social Media Advertising, Word of Mouth And Brand Image As Intervening Variables - Marlita Wulansari; Bartolomius Dias; Arief Nurrahman (JURNAL ILMU MANAJEMEN, 2025)
Le Minerale is one of the bottled water brands that is in great demand by the public. This means that the product must continue to innovate to maintain its position as the top brand of drinking water in Indonesia. This study aims to analyze the influence of social media advertising and word of mouth on consumer buying interest with brand image as an intervening variable. This study used a quantitative method through a questionnaire to 115 respondents who were Gen Z. The data analysis technique used was PLS SEM analysis to examine the inter-variables of the study. The results of the study show that social media advertising and word of mouth have a positive effect on brand image, which in turn affects consumer purchase interest in Le Minerale products. These findings underline the importance of being the brand's mind through social media advertising and socializing with the public about Le Minerale products to attract their buying interest.